Recently targeted kinases and their inhibitors-the path to clinical trials. - Knapp, S; Sundström, M (Elsevier, 2014)
Protein kinases have emerged as one of the most important drug target families for the treatment of cancer. To date, 28 inhibitors with reported activity versus one or multiple kinases have been approved for clinical use. However, the majority of new clinical trials are focused on new subindications using already approved kinase inhibitors or target well validated kinase targets with novel inhibitors. In contrast, relatively few clinical trials have been initiated using specific inhibitors that inhibit novel kinase targets, despite significant validation efforts in the public domain. Analysis of the target validation history of first in class kinase inhibitors revealed a long delay between initial disease association and development of inhibitors. As part of this analysis, we have investigated which first in class inhibitor that entered phase I clinical trials over the last five years and also considered which research approaches that were used to validate them.